LEGAL IMPLICATIONS OF THE JOB CREATION LAW ON THE POSITION OF DIRECTORS IN INDIVIDUAL COMPANIES - Nor Muhamad; Abraham Ferry Rosando (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
The enactment of Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation into Law (Job Creation Law) has brought fundamental changes to the concept of the Limited Liability Company (PT) legal entity in Indonesia. Significant changes occurred in Article 1 number 1 and Article 7 of Law Number 40 of 2007 concerning Limited Liability Companies (UUPT), which now introduces the concept of a Sole Proprietorship (Private Liability Company) for Micro and Small Enterprises (MSEs). Unlike the classic principle of a PT, which is a capital association and must be established by at least two individuals based on an agreement, a Sole Proprietorship allows for the establishment of a single individual through a deed of establishment. However, the Job Creation Law does not change the provisions regarding the Company's Organs, which consist of the General Meeting of Shareholders (GMS), the Board of Directors, and the Board of Commissioners, which are generally assumed to be held by different individuals. This study aims to examine and analyze the status and mechanisms of Limited Liability Company Organs in Sole Proprietorships categorized as micro and small enterprises, considering the combination of the functions of capital owner and manager within a single legal entity.